The Effect of Submucosal Injection of Plasma-Rich Platelets on Blood Inflammatory Markers for Patients with Bimaxillary Protrusion Undergoing Orthodontic Treatment - Trefa Mohammed Ali Mahmood; Omar Fawzi Chawshli (International Journal of Inflammation)
Objectives. The present study aims to reveal the systemic effects of submucosal injection of plasma-rich platelets (PRP) on blood inflammatory markers which was used in an attempt to reduce the retraction time of the upper canine following extraction of upper maxillary premolars for patients with bimaxillary protrusion. Hypothesis. No change on comparing the values of blood inflammatory markers before and after submucosal injection of PRP. Methods. Eighteen female patients with bimaxillary protusion were selected from patients seeking orthodontic treatment from the College of Dentistry/University of Sulaimai, whose maxillary and mandibular first premolars were decided to be extracted after proper diagnosis. Thirty-three blood markers (twenty hematological and thirteen biochemical markers) were estimated before orthodontic bracketing, 24 hours and 7 days following submucosal injection of PRP (5 cc) to reveal the systematic effect of PRP on blood inflammatory markers that were used in an attempt to reduce the retraction time of the upper canine following extraction of upper maxillary premolars for patients with bimaxillary protrusion. Results. The results indicate nonsignificant differences in the values of all blood markers except for gamma GT (GGT), PDWa, serum albumin, serum total protein, and total calcium. Gamma level significantly increased for both test intervals. On the other hand, there was a significant drop in the value of PDWa while for alkaline phosphatase, there was a drop within the first 24 hr of PRP injection while after 7 days the value was significantly increased. On the other hand, there was a drop in the level of serum albumin, while there was an increase in the serum total protein and total calcium. Conclusion. Submucosal injection of PRP could lead to systematic alteration of blood parameters including ALK phosphatase, gamma GT, serum albumin, and serum total protein, which may be related to liver function in addition to increase in the level of PDWa and serum calcium. We present evidence that PRP contains and may trigger systemic effect. Thus, further investigation is recommended to follow up the patient for a longer period of time and on a larger sample. This trial is registered with U1111-1221-8829 by Sri Lanka Clinical Trial Registry, SLCTR/2018/040, and No. 64 on 6th August 2018 at the local clinical studies database, College of Dentistry.